Lokacije in tipi spremljajočih objektov ob avtocestah v Republiki Sloveniji - Jagodič, Boris (Urbani izziv, 1994)
The article is a summary of a few chapters of the research The locations and types of complementary activities on Slovene highways. The number of complementary locations, regulations concerning constructions and types of complementary locations are thoroughly discussed. Emphasis is given to the modification of criteria, which apply to the positioning of complementary activities on highways, amongst other because of small dimensions of available land, characteristics of the terrain and the polycentric pattern of settlemnts.
Keywords: avtoceste; environmental protection; krajinska arhitektura; prostorsko planiranje; prostorsko urejanje; Slovenia; Slovenija; spatial planning; varstvo okolja